Degradation of HaloTag-fused nuclear proteins using bestatin-HaloTag ligand hybrid molecules1. Issue 38 (14th October 2015) - Tomoshige, Shusuke; Naito, Mikihiko; Hashimoto, Yuichi; Ishikawa, Minoru
<x xml:space="preserve">Abstract</x> We successfully knocked down HaloTag-fused nuclear proteins in living cells by using protein knockdown technology.